Religion and the Body Modern Science and the Construction of Religious Meaning - Cave, David; Sachs Norris, Rebecca (Numen Book Series, 2012)
This book reflects on the implications of neurobiology and the scientific worldview on aspects of religious experience, belief, and practice, focusing especially on the body and the construction of religious meaning. Readership: All those interested in neurobiology and religion, contemporary culture and religion, theology and embodiment, anthropology, sociology, and psychology of religion, including scholars, students, educated laymen, academic and public libraries.